Protein Deficiency-Induced Behavioral Abnormalities and Neurotransmitter Loss in Aged Mice Are Ameliorated by Essential Amino Acids - Sato, Hideaki; Tsukamoto-Yasui, Masako; Takado, Yuhei; Kawasaki, Noriko; Matsunaga, Keiko; Ueno, Satoko; Kanda, Mayuka; Nishimura, Mai; Karakawa, Sachise; Isokawa, Muneki; Suzuki, Katsuya; Nagao, Kenji; et al. (Frontiers in Nutrition, 2020)
Nutritional epidemiology shows that insufficient protein intake is related to senile dementia. The levels of protein intake in aged people are positively associated with memory function, and elderly people with high protein intake have a low risk of mild cognitive impairment. Although the beneficial roles of protein nutrition in maintaining brain function in aged people are well demonstrated, little is known about the mechanism by which dietary intake of protein affects memory and brain conditions. We fed aged mice a low protein diet (LPD) for 2 months, which caused behavioral abnormalities, and examined the nutritional effect of essential amino acid administration under LPD conditions. The passive avoidance test revealed that LPD mice demonstrated learning and memory impairment. Similarly, the LPD mice showed agitation and hyperactive behavior in the elevated plus maze test. Moreover, LPD mice exhibited decreased concentrations of gamma-aminobutyric acid (GABA), glutamate, glycine, dopamine, norepinephrine, serotonin and aspartate in the brain. Interestingly, oral administration of seven essential amino acids (EAAs; valine, leucine, isoleucine, lysine, phenylalanine, histidine, and tryptophan) to LPD mice, which can be a source of neurotransmitters, reversed those behavioral changes. The oral administration of EAAs restored the brain concentration of glutamate, which is involved in learning and memory ability and may be associated with the observed behavioral changes. Although the details of the link between decreased amino acid and neurotransmitter concentrations and behavioral abnormalities must be examined in future studies, these findings suggest the importance of dietary protein and essential amino acids for maintaining brain function.